(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2025)
The research aimed to identify the obstacles to applying visual management in kindergarten institutions, and to reveal the existence of significant differences between the average estimates of the total sample in determining the obstacles to its application depending on (the supervising body, years of experience, and academic qualification, Job title). The researcher used the descriptive analytical method based on a “research tool” questionnaire, the number of which was (45) items distributed over four axes as follows: human obstacles (12) items, organizational obstacles (12) items, administrative obstacles (12) items, and obstacles Finance (9 items), and the original community consisted of all kindergarten principals and teachers in the city of Damascus, and the research sample was limited to (95) manager and (235) kindergarten teachers who were chosen randomly. The research reached a set of results, the most important of which are: • The arithmetic averages of the research sample’s answers to the axes of obstacles to implementing visual management in kindergarten institutions were limited between (3.96 and 4.38), and the axis that ranked first was the axis of financial obstacles, followed by administrative obstacles, in third place were human obstacles, and in fourth place were organizational obstacles. All of these obstacles were at a high level. • There are no significant differences between the average scores of the responses of the research sample members regarding the obstacles to applying visual management in kindergarten institutions according to the supervisory authority variable, while the results showed that there are significant differences according to the “years of service” variable in favor of the sample members who have more than 5 years of service and less. From 10 years, and those with 10 or more years of service. The academic qualification variable is in favor of higher academic qualifications. The most important research proposals are: • Holding educational and awareness sessions for teachers and administrators about the benefits and uses of visual management and the mechanism for applying it effectively in kindergarten institutions. • Encouraging continuous communication between administration and teachers, and providing platforms for cooperation and exchange of ideas to enhance the effective use of visual management. • Promoting a culture of innovation and continuous improvement in educational institutions, and encouraging the use of new technologies and advanced tools. • Conducting research on the role of organizational culture in enhancing the concepts of applying visual management in kindergarten institutions.